2019
DOI: 10.1186/s12937-019-0512-9
|View full text |Cite
|
Sign up to set email alerts
|

Empirically derived dietary patterns and constipation among a middle-aged population from China, 2016–2018

Abstract: BackgroundThe association of dietary patterns with constipation is not well established, particularly in Chinese population. Therefore, the present study aimed to determine the relationship between dietary patterns and the risk of constipation in a middle-aged Chinese population.MethodsA total of 2267 participants aged 45–59 years were recruited in Hangzhou city, the capital of Zhejiang Province, east China from August 2016 to October 2018. Dietary intake was estimated using a semi-quantitative food frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Ongoing monitoring of dietary habits can provide data for nutrition policy development and offer evidence of the impact of the nutrition transition occurring in China. Dietary patterns have been frequently assessed in Chinese studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, studies that assessed how the patterns change over time are considerably less frequent [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing monitoring of dietary habits can provide data for nutrition policy development and offer evidence of the impact of the nutrition transition occurring in China. Dietary patterns have been frequently assessed in Chinese studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, studies that assessed how the patterns change over time are considerably less frequent [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that a sedentary lifestyle, dietary habits and types such as low vegetable and fruit intake (low dietary fiber), inadequate water intake, and low levels of education all contribute to an increased prevalence of FC [ 7 , 12 , 13 ]. In addition to the known factors described above, the prevalence of FC may be associated with sleep status.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, refined sugary products have been implicated in many gastrointestinal disorders [ 63 ], especially in constipation, as these are typically low in fiber and often also high in unhealthy fats [ 36 ]. Some studies have shown that frequent consumption of sugary snacks was linked to increased odds of constipation [ 64 ]. On some occasions, excess intake of certain sugars such as fructose [ 65 ] and polyols [ 65 ] may be related to very loose stools due to the osmotic effect of these sugars in the gut [ 65 ].…”
Section: Discussionmentioning
confidence: 99%